Comparison of singlet oxygen production of ethyl vanillin substituted silicon phthalocyanine using sonophotodynamic and photodynamic methods - Karanlik, Ceren Can; Yasa, Goknur; Erdogmus, Atmaca Ali (ELSEVIER, 2023)
Although Sonophotodynamic Therapy (SPDT) studies, which are a new approach that give better results than Photodynamic Therapy (PDT) in which light and sound are used together, are encountered in the literature, studies in this area are limited. Therefore, this study aimed to demonstrate the potentials of the synthesized compound in PDT and SPDT applications. While the calculated OA value was 0.50 for compound 1 after light irradiation, this value increased to 0.81 after light and ultrasound irradiation were used together. When the PDT and SPDT methods were compared, it proved that the singlet oxygen production increased significantly when the excitation method was changed to light and ultrasound. This study will enrich the literature on increasing singlet oxygen production by SPDT method. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Sonophotodynamic therapy; Photodynamic therapy; Silicon phthalocyanine; Singlet oxygen; VITRO ANTICANCER ACTIVITY; IN-VITRO; NANOPARTICLE; PHOTOSENSITIZER; DERIVATIVES; Chemistry